Older patients with anomalous origin of the pulmonary artery from the ascending aorta: Guidance via lung biopsy. Issue 2 (6th November 2019) - Zhao, Junfei; Si, Ming‐Sing; Wang, Xiaoyan; Chen, Siyao; Yan, Qian; Chen, Jimei
Abstract: Anomalous origin of one pulmonary artery from the ascending aorta is a rare congenital cardiac anomaly characterized by progressive pulmonary arterial hypertension (PAH) and pulmonary vascular obstructive disease (PVOD) in early childhood. This condition is assumed to be inoperable in older children and adults. However, pulmonary vascular resistance of the isolated lung is difficult to measure by catheterization due to its unique anatomical features, and thus we have used lung biopsy as an alternative method to evaluate candidacy for repair. Here, we report our experience with two patients whose lung biopsy demonstrated reversible PVOD, leading us to perform a surgical repair.